2014
DOI: 10.3109/13816810.2014.907921
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of GST and FTO Genes in Risk Prediction of Cataract among a North Indian Population

Abstract: The present study suggested that GSTM1, GSTT1 and FTO gene polymorphisms are associated with increased risk for cataract in North Indian populations. Due to the limited sample size, the finding on GST and FTO gene polymorphisms need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, a comparison of the case group in this study with the case and control groups reported by Çelįk et al (2015) with respect to the GSTT1 polymorphisms showed very different results (P < 0.001), suggesting a correlation between the null GSTT1 polymorphism and the development of cataract. Our study was also corroborated by a previous study conducted by Chandra et al (2016) in northern India, who reported that the GSTM1 and GSTT1 polymorphisms were associated with increased risk of cataract development. Further, Saadat et al (2012) reported that the GSTM1-null genotype increased the risk of developing this pathology in an Iranian population.…”
Section: Discussionsupporting
confidence: 80%
“…However, a comparison of the case group in this study with the case and control groups reported by Çelįk et al (2015) with respect to the GSTT1 polymorphisms showed very different results (P < 0.001), suggesting a correlation between the null GSTT1 polymorphism and the development of cataract. Our study was also corroborated by a previous study conducted by Chandra et al (2016) in northern India, who reported that the GSTM1 and GSTT1 polymorphisms were associated with increased risk of cataract development. Further, Saadat et al (2012) reported that the GSTM1-null genotype increased the risk of developing this pathology in an Iranian population.…”
Section: Discussionsupporting
confidence: 80%
“…Flow diagram of studies included in this meta-analysis is provided in Figure 1 . Fifteen studies [ 18 – 32 ] were included in the meta-analysis of the GSTM1 genotype (3165 cases, 2105 controls), and nine studies were included in the meta-analysis of GSTT1 (2374 cases, 1544 controls). For the meta-analysis of GSTM1 , six studies on Asians and nine on Caucasians were included.…”
Section: Resultsmentioning
confidence: 99%
“…They have found a two-fold risk of developing senile cortical cataracts associated with the GSTM 1-positive phenotype. Similarly Chandra et al [21] also found 1.9 (95% Cl: 1.08-3.32) risk of developing cataract with the GSTM 1-positive phenotype in Indian population. However, GSTT 1-positive phenotype has protective effect (OR: 0.27, 95% CI, 0.09-0.86) was determined in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have indicated that GST enzymes may play a role in cataract predisposition with different GST phenotypes [16,[20][21][22][23] but no associations were found in another study [24].…”
mentioning
confidence: 99%